Antigenic characterization of recombinant hemagglutinin proteins derived from different avian influenza virus subtypes. - Matthias Mueller (Public Library of Science (PLoS), 2010)
Since the advent of highly pathogenic variants of avian influenza virus (HPAIV), the main focus of avian influenza research has been the characterization and detection of HPAIV hemagglutinin (HA) from H5 and H7 subtypes. However, due to the high mutation and reassortation rate of influenza viruses, in theory any influenza strain may acquire increased pathogenicity irrespective of its subtype. A comprehensive antigenic characterization of influenza viruses encompassing all 16 HA and 9 neuraminidase subtypes will provide information useful for the design of differential diagnostic tools, and possibly, vaccines. We have expressed recombinant HA proteins from 3 different influenza virus HA subtypes in the baculovirus system. These proteins were used to generate polyclonal rabbit antisera, which were subsequently employed in epitope scanning analysis using peptide libraries spanning the entire HA. Here, we report the identification and characterization of linear, HA subtype-specific as well as inter subtype-conserved epitopes along the HA proteins. Selected subtype-specific epitopes were shown to be suitable for the differentiation of anti-HA antibodies in an ELISA.